BENTUK, FUNGSI DAN MAKNA MOTIF BATIK BASUREK BENGKULU - ANDI SAPUTRA, Drs. Erwin, M.Sn, Yofita Sandra, S.Pd., M.Pd (Serupa The Journal of Art Education, 2014)
The study aims to :1) describe shape of batik basurek, 2)describe purposes of batik, and 3) describe of meaning batik basurek.This research is descriptive qualitative. The data sources are theprimary source directly by the informant, while secondary data wasfrom the documentation and bibliography. The data collectedthrough the initial review, the study of literature, observation,interviews, documentation. The findings of the study are kaligrafymotif, burung kuau, kembang melati, relung paku, kembangcengkeh, dan pohon hayat. Basurek functions such as batik scarf,headband, baby swing fabrics and trimmings pegantin booth.Meaning basurek motif is a depiction of the natural resources inBengkulu and form of gratitude towards God's creation.Kata Kunci : Bentuk, Fungsi dan Makna Motif Batik Basurek